Esomeprazole use is independently associated with significant reduction of BMD: 1-year prospective comparative safety study of four proton pump inhibitors - Bahtiri, E.; Islami, H.; Hoxha, R.; Qorraj-Bytyqi, H.; Rexhepi, S.; Hoti, Kreshnik; Thaçi, K.; Thaçi, S.; Karakulak, . (Springer-Verlag Tokyo, 2015)
© 2015 The Japanese Society for Bone and Mineral Research and Springer Japan Because of the efficacy of proton pump inhibitors (PPIs), their the use is increasing dramatically. The risk of adverse effects of short-term PPI therapy is low, but there are important safety concerns for potential adverse effects of prolonged PPI therapy. Findings from studies assessing the association between PPI use and bone mineral density (BMD) and/or fracture risk are contradictory. The aim of this study was to prospectively assess potential association of PPI treatment with the 12-month change in BMD of the lumbar spine, femur neck, and total hip. The study was performed in 200 PPI users and 50 PPI nonusers. Lumbar spine (L1–L4), femur neck, and total hip BMD were measured by dual-energy X-ray absorptiometry at the baseline and at 12 months. A total of 209 subjects completed the entire 12 months of the study and were included in the final analysis. A Wilcoxon signed-rank test showed that at 12 months PPI use was associated with statistically significant reductions in femur neck and total hip T scores (Z = -2.764, p = 0.005 and Z = -3.281, p = 0.001, respectively). A multiple linear regression analysis showed that only esomeprazole added significantly to the prediction of total lumbar spine and femur neck T scores (p = 0.048 and p = 0.037, respectively). Compared with the baseline, 12 months of PPI treatment resulted in lower femur neck and total hip BMD T scores. Among the four PPIs studied, esomeprazole was independently associated with significant reduction of BMD, whereas omeprazole had no effects on BMD. Considering the widespread use of PPIs, BMD screening should be considered in the case of prolonged PPI use.